Penerapan Metode Multi-Attributive Border Approximation Area Comparison Dalam Rekomendasi Pemilihan Mobil Second - Badiwibowo Atim, Sandi (PT. Tech Cart Press, 2024)
Used cars or often referred to as second cars, are a popular choice for many consumers because they offer more affordable value compared to new cars. Used vehicles often have lower prices, which makes them more accessible to many people. The application of the MABAC method in used car selection recommendations helps consumers to make more informed and informed decisions. By using MABAC, important factors such as physical condition, price, vehicle age, completeness of documents, and fuel efficiency. This method allows buyers to evaluate used cars based on their personal preferences and needs, resulting in recommendations that better fit the desired criteria. The results of the secong car selection recommendation are Alternative 2 with a final value of 0.921 getting rank 1, then Alternative 3 with a final value of 0.821 getting rank 2, and Alternative 4 with a final value of 0.621 getting rank 3.